The educational blogosphere: new university spaces of innovation and teacher training within the european context - José Ignacio Aguaded Gómez; Eloy López Meneses (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The social software for university teacher training has become a key factor in the experiences of pedagogical innovation at universities within the context of the new challenges in the European Space. This study offers up an experience for didactic use of the blogs of 136 students from the 2008/09 year from a socio-constructive and investigative perspective. Using the blogs covering various university subjects, the conclusion drawn under this paradigm is that blogs are easy-to-use telematic tools in university teaching that greatly encourage students to take an active role, as well as being invaluable tools in assessing that the practical results of that teaching. In sum, blogs are an emerging resource in the educational field.